Schaum's Outline programming with Pascal / with emphasis on Turbo Pascal with features of standard Ansi Pascal - Gottfried Byron S. (New York : McGraw-Hill, 1994)
This book offers instruction in computer programming at most colleges and universities. many high schools and community colleges also offer introductory or secondary programming courses in Pascal
includes index
aau 17/08/2022
loan
Keywords: Computer program language